2020
DOI: 10.1103/physrevresearch.2.043062
|View full text |Cite
|
Sign up to set email alerts
|

Measure of qubit-environment entanglement for pure dephasing evolutions

Abstract: We propose a qubit-environment entanglement measure which is tailored for evolutions that lead to pure dephasing of the qubit, such as are abundant in solid-state scenarios. The measure can be calculated directly form the density matrix without minimization of any kind. In fact, it does not require knowledge of the full density matrix and it is enough to know the initial qubit state and the states of the environment conditional on qubit pointer states. This yields a computational advantage over standard entang… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…[57]. It has later been shown that the periodical emergence of such states is possible in qubit-environment evolutions driven by Hamiltonians that lead to pure dephasing of the qubit [19] and are important for the emergence of objectivity [58][59][60][61][62][63][64]. Here we have found that the emergence of such states is not limited to pure-dephasing evolutions and that they can manifest themselves in other classes of interactions.…”
Section: Consequencessupporting
confidence: 51%
See 2 more Smart Citations
“…[57]. It has later been shown that the periodical emergence of such states is possible in qubit-environment evolutions driven by Hamiltonians that lead to pure dephasing of the qubit [19] and are important for the emergence of objectivity [58][59][60][61][62][63][64]. Here we have found that the emergence of such states is not limited to pure-dephasing evolutions and that they can manifest themselves in other classes of interactions.…”
Section: Consequencessupporting
confidence: 51%
“…The quest to find efficiently computable entanglement measures that have a clear physical interpretation continues [19][20][21], because entanglement remains an important factor which predetermines the possibility of very quantum and nonintuitive behavior of bipartite systems. One approach is to sacrifice generality in order to obtain solvable scenarios which allows for the study of entanglement present in density matrices generated by a certain class of Hamiltonians.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The qubit-environment entanglement measure tailored to pure dephasing evolutions, which was introduced in Ref. [35], can be used to quantify the amount of entanglement in the CE state in eq. (10).…”
Section: Teleportation With the Help Of Decohered Bell Statementioning
confidence: 99%
“…respectively, while the condition of separability of qubit C and the environment pre-teleportation and decoherence ( 10) is R00 (τ) = R11 (τ). Hence, if there is no entanglement after the first part of teleportation then both states are either entangled or separable, and the amount of entanglement in the two states is also the same [35], as it is quantified by a function analogous to eq. ( 12),…”
Section: Simultaneous Transfer and Teleportation Of Correlationsmentioning
confidence: 99%